2019
DOI: 10.1097/meg.0000000000001272
|View full text |Cite
|
Sign up to set email alerts
|

Role of the von Willebrand factor and the VITRO score as predictors for variceal bleeding in patients with hepatitis C-related cirrhosis

Abstract: Background Noninvasive methods have been established to detect clinically significant portal hypertension in liver cirrhosis with variable limitations. The von Willebrand factor (vEF) has been found to increase in liver cirrhosis. Aim The aim of this study was to explore the vEF and VITRO (von Willebrand factor antigen/platelet ratio) score in the prediction of variceal bleeding in patients with portal hypertension. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
4
0
1
Order By: Relevance
“…The multivariate analysis for possible confounding factors revealed that VWF was independently correlated to the esophageal varices and that none of these variables correlated to the VWF confounded its relation to the esophageal varices. This comes in agreement with Ibrahim et al [19] who found that VWF is an independent predictor of variceal bleeding [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The multivariate analysis for possible confounding factors revealed that VWF was independently correlated to the esophageal varices and that none of these variables correlated to the VWF confounded its relation to the esophageal varices. This comes in agreement with Ibrahim et al [19] who found that VWF is an independent predictor of variceal bleeding [19].…”
Section: Discussionsupporting
confidence: 91%
“…In our study we found that the VITRO score was significantly higher among patients of group I than in group II. This agrees with Hassan et al[18] and Ibrahim et al[19] who said that the VITRO score was significantly higher in patients with varices[18,19]. This may be the reason that the association between VWF and the hepatic decompensation was not clear in study.…”
supporting
confidence: 87%
“…No association was observed between platelet count and bleeding. Two studies addressing variceal bleeding found opposite results regarding the association between platelet count and bleeding [20,21]. It is, however, important to stress that platelet count may merely reflect the degree of portal hypertension responsible for variceal hemorrhage [22].…”
Section: Studies On Cld and Platelet Countmentioning
confidence: 99%
“…A decade ago, researchers tried to exploit metabolic data to predict HVPG and found that the homeostasis model assessment index was associated with high risk of EVB[ 15 ]. Ibrahim et al [ 16 ] reported that the serum vWF antigen level and vWF antigen/platelet ratio (VITRO) could help stratify the risk of bleeding, with AUCs of 0.982 and 0.843, respectively, although this study had a small sample size. Kothari et al [ 17 ] argued that the platelet count-to-spleen diameter ratio and FIB-4 index might be useful for predicting EVB, with AUCs of 0.78 and 0.74, respectively.…”
Section: Modalities For Evaluating Evb Riskmentioning
confidence: 86%